Symmetry dimethylarginine (SDMA) assay for diagnosis of kidney disease in dogs and cats: a mini review of case reports in Indonesia - Fitriya Nur Annisa Dewi; Sus Derthi Widhyari; Arief Purwo Mihardi; Setyo Widodo; Anita Esfandiari (ARSHI Veterinary Letters, 2024)
Symmetry Dimethylarginine (SDMA) is an important biomarker for early diagnosis of kidney disease. Studies suggest that SDMA is a more sensitive indicator of kidney function compared to traditional markers such as blood urea nitrogen (BUN) and creatinine. Since 2015, the International Renal Interest Society (IRIS) has established SDMA as one of the indicators for diagnosis and determining the stage of chronic kidney disease (CKD) in dogs and cats. SDMA assay use in veterinary clinics in Indonesia has empirically become more common. The aim of this study was to identify scientific reports on SDMA assay use in the diagnosis of kidney disease in dogs and cats in Indonesia. We performed a literature search in the Garuda portal and Google Scholar using the following keywords: “SDMA” or “Symmetry Dimethylarginine”, “dogs”, “cats” and “Indonesia”. The search strategy utilized English and Bahasa Indonesia, and the results were screened for relevance to the topic, and limited to studies conducted in Indonesia. Seven scientific articles in national and international journals reported the use of SDMA assay in cases of kidney disease in dogs or cats in Indonesia, published between 2021-2023. It is expected that SDMA assay use will continue to increase in veterinary practice settings in the country, and it is therefore critical to have a proper understanding of the advantages and limitations of SDMA use for kidney disease diagnosis.